The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Extended Abstracts of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411763.3451643
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Asynchronous Participatory Design of Open Source Software: Bringing End Users into the Loop

Abstract: As open source software (OSS) becomes increasingly mature and popular, there are significant challenges with properly accounting for usability concerns for the diverse end users. Participatory design, where multiple stakeholders collaborate on iterating the design, can be an efficient way to address the usability concerns for OSS projects. However, barriers such as a code-centric mindset and insufficient tool support often prevent OSS teams from effectively including end users in participatory design methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In particular, the insights from the 'Clout', 'Tone', 'Authentic', and 'Affect' categories show that end-users in all four forums are significantly less confident than the organizers, but are simultaneously more divulging, open, and positive in their communications. Since the current OSS development process often overlooks the contributions from end-users [9,38], some end-users can be reluctant or apprehensive to use forums unless it is a last resort for obtaining help [9]. This is likely reflected in the end-user LIWC results with the low 'Clout' scores but higher 'Tone', 'Authentic', and 'affect'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the insights from the 'Clout', 'Tone', 'Authentic', and 'Affect' categories show that end-users in all four forums are significantly less confident than the organizers, but are simultaneously more divulging, open, and positive in their communications. Since the current OSS development process often overlooks the contributions from end-users [9,38], some end-users can be reluctant or apprehensive to use forums unless it is a last resort for obtaining help [9]. This is likely reflected in the end-user LIWC results with the low 'Clout' scores but higher 'Tone', 'Authentic', and 'affect'.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [38] advocated for the need for a usercentric and inclusive mindset amongst OSS practitioners. Hellman et al [9] identified inclusiveness and learnability of issue tracking as barriers for non-technical OSS end-users to collaborate on a project in addition to OSS designers and developers struggling to manage multiple sources for end-user engagement. Most prior work on OSS forums and discussions has focused on developer forums, discussions, or mailing lists but not the end-user specific forums [4,19,31,35].…”
Section: Background and Related Work 21 Oss Usability And Forumsmentioning
confidence: 99%
“…Open-source software is diffused at the level of artificial artifacts [82,83]. The essence of open-source diffusion is the shared spreading of source code and technical documentation as well as asynchronous participatory innovative iterations [84]. Community-driven operation facilitates rapid software diffusion [85], and open-source software developers interact with users on community platforms to acquire user needs and proactively address relevant user issues, thus providing technical support and upgrade services to increase user retention and loyalty.…”
Section: Open-source Diffusionmentioning
confidence: 99%